2018
DOI: 10.1182/blood-2018-04-845065
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of clonal evolution in patients with concurrent myelo- and lymphoproliferative neoplasms

Abstract: BCR-ABL-negative myeloproliferative neoplasms (MPNs) are a group of clonal stem cell disorders characterized by the overproduction of mature myeloid cells. However, MPN patients also have a 2.8-to 3.4-fold increased risk of developing a lymphoproliferative disorder (LPD) compared with the general population. 1,2 A range of lymphoid neoplasms have been documented in MPN patients, most commonly chronic lymphocytic leukemia (CLL), which can be diagnosed prior to, simultaneous with, or following the myeloid neopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Although our somatic mutational analyses clearly demonstrate the existence of common lymphoid and myeloid leukemia progenitors and are consistent with some previous studies, 23,24 we recognize that not all reported cases show a clonal relationship by targeted gene sequencing between concurrent or sequentially developed lymphoid and myeloid tumors. 25 However, analysis of these types of cases using WES may be more informative, as evidenced by the cases presented here.…”
Section: Cll Cells Convert To Myeloid Lineage In Vivomentioning
confidence: 89%
“…Although our somatic mutational analyses clearly demonstrate the existence of common lymphoid and myeloid leukemia progenitors and are consistent with some previous studies, 23,24 we recognize that not all reported cases show a clonal relationship by targeted gene sequencing between concurrent or sequentially developed lymphoid and myeloid tumors. 25 However, analysis of these types of cases using WES may be more informative, as evidenced by the cases presented here.…”
Section: Cll Cells Convert To Myeloid Lineage In Vivomentioning
confidence: 89%
“…Biologically, it has been speculated that the co-occurrence of myeloid and lymphoid neoplasms may be sustained by a common clonal progenitor ( 13 , 14 ). This could be assumed particularly in MPN patients with a demonstrated driver mutation, preceding LPD onset.…”
Section: Discussionmentioning
confidence: 99%
“…In their series, the pathogenic development of concurrent MPN/LPD was either an independent origin with a role for environmental factors or a germ-line predisposition with a common clonal origin but without mutations in age-related clonal hematopoiesis drivers. 8 Focusing on JAKi treatment, RUX affects several genes found in lymphoid cancer stem cells, thus causing the pathological expression of transcription factors that have a role in lymphomagenesis, neoplastic engagement on lymphoid progenitor cells, inhibition of apoptosis, and subsequent promotion of neoplastic proliferation of malignant neoplastic lymphoma cells. 9 Considering the published studies evaluating the correlation between MPN and LPD, which show different results (Pemmaraju et al and Porpaczy et al), we still need further data to have a definitive answer.…”
Section: Occurrence Of Lymphoproliferative Disorders During Ruxolitin...mentioning
confidence: 99%